2009
DOI: 10.1080/09687760903033082
|View full text |Cite
|
Sign up to set email alerts
|

Beyond podcasting: creative approaches to designing educational audio

Abstract: This paper discusses a university-wide pilot designed to encourage academics to creatively explore learner-centred applications for digital audio. Participation in the pilot was diverse in terms of technical competence, confidence and contextual requirements and there was little prior experience of working with digital audio. Many innovative approaches were taken to using audio in a blended context including student-generated vox pops, audio feedback models, audio conversations and task-setting. A podcast was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 4 publications
3
36
0
2
Order By: Relevance
“…Students felt "hearing other people's voices helps to make a more personal connection to them". This suggests that audio communication did help to reduce feelings of isolation among students, confirming the increased social presence afforded by asynchronous audio reported by Middleton (2009) and Lee and Chan (2007). The second theme was the opportunity for students on this module to practise speaking, pronunciation and listening skills.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…Students felt "hearing other people's voices helps to make a more personal connection to them". This suggests that audio communication did help to reduce feelings of isolation among students, confirming the increased social presence afforded by asynchronous audio reported by Middleton (2009) and Lee and Chan (2007). The second theme was the opportunity for students on this module to practise speaking, pronunciation and listening skills.…”
Section: Resultssupporting
confidence: 70%
“…These studies show that students producing podcasts for their peers can promote collaborative peer-to-peer learning and individual reflection and cognition, as well as develop transferable skills such as communication skills, teamwork and problem-solving. Middleton (2009) suggests that the use of audio in online environments that had been predominantly text-based made them a more 'human space' by increasing the feeling of social presence; lack of social presence and feelings of isolation have been found to be a barrier to online learning (Muilenburg and Berge 2005;Newberry 2001).…”
Section: Background and Rationalementioning
confidence: 99%
“…A recent innovation is the use of audio feedback (Middleton 2009), although to date studies and practice have remained small-scale despite personal recording devices being readily available and recording software relatively easy to use. In a recent study by Rodway-Dyer, Dunne, and Newcombe (2009) of first-year students receiving audio feedback, they found that the main advantage was the greater detail and depth of information offered, as well as removing misunderstandings due to illegible handwriting.…”
Section: Producing Feedback Electronicallymentioning
confidence: 99%
“…Although previous studies have noted that the reproduction of lectures may lead to benefits (Brittain et al 2006) such as providing the lecture for those who did not attend and a record to support revision (Evans 2008), the students who took part in the current study suggested that the reproduction of a lecture in the form of a podcast is not useful. In fact, researchers point out that the strategy of simply reproducing lectures in podcasts is in conflict with learning theories that advocate richer and more active learning experiences for learners (Middleton 2009). Another reason that may account for the low rating of informational podcasts is the time of conducting the survey and the interviews.…”
Section: Dissemination and Downloadingmentioning
confidence: 99%